Alagille Syndrome and Its Clinical and Laboratory Features: A Case Report - Ludovico Abenavoli; Luigi Boccuto; Alessandro Corea; Marialuisa Gambardella; Rocco Spagnuolo; Francesco Luzza (Livers, 2022)
Alagille syndrome (ALGS) is a genetic-driven condition of chronic cholestasis, involving the intrahepatic bile ducts, heart, vessels, kidneys, skeletal tissues, eyes, and nervous system. Pathological mechanisms are still not defined. JAG1 and NOTCH2 gene mutations are responsible for most cases (96–97%). Diagnosis is based on clinical and laboratory findings—especially the presence of chronic cholestasis—and on genetic assessment. Bone abnormalities, deficiency of liposoluble vitamins, heart issues, and pruritus are the most prominent features of ALGS. Diagnostic imaging, such as ultrasonography, magnetic resonance imaging, and bone mass density assessment, is useful to study hepatic disease progression, estimate the risk of bone fracture, and rule out malignities. Therapy is based on ursodeoxycholic acid, rifampicin, cholestyramine, and supplementation of liposoluble vitamins. New therapeutic approaches are under investigation. Here, we describe a case of an individual with ALGS presenting with congenital chronic cholestasis and a long clinical history, in which pruritus is the main symptom.